Estimation of carbon dioxide potential stored in the aerial biomass of the Chaviña Wetlands, Arequipa, Peru - Ttito Rado, Karen (2024)
This study focused on analyzing the carbon storage capacity of the Chaviña wetlands, the objective was to estimate the carbon stock present in the aerial biomass. For this purpose, 17 samples were obtained randomly using a 0.25 m2 quadrat. Subsequently, each sample underwent a drying process in an oven at a temperature of 60°C for periods of 24 to 72 hours, until they reached a constant weight. Next, the Walkley and Black method was applied to determine the carbon content in each of the samples. Finally, calculations were made to obtain the carbon stock stored in the aerial biomass. Additionally, statistical tests were carried out to identify the differences between the percentage of carbon in the aboveground biomass and the carbon stored in the aboveground biomass by marsh level (high, medium and low). The results obtained indicate that there are no significant differences in the carbon stock between the three marsh levels. In addition, it was quantified that the wetland biomass stores a total of 18 628 tC and sequesters 70 904 tCO2. This finding shows the relevance of the Chaviña Wetlands as a significant carbon reservoir.